Running shoe knowledge and purchasing decisions compared among groups of athletes - Low, Nicole Sui Xuan (Nanyang Technological University, 2020)
Background: Recommending running shoes (RS) based on arch types has shown to be effective in reducing running related injures (RRI). Knowledge of RS should be assessed and compared amongst runners and ball sport athletes (BSA) to provide targeted education. Factors influencing RS purchase decisions should be examined to provide greater insight for manufactures when designing RS. Purpose: The purpose of this study was to (i) assess and compare the knowledge of RS and arch types between runners and BSA, (ii) identify the main factors that affect RS purchase decisions. Hypotheses: H1: Runners would have better knowledge of RS and arch types than BSA. H2: Price, aesthetics, social influences, branding and comfort would be the top factors influencing RS purchase decisions. H3: More athletes would prefer aesthetics to comfort. Method: 119 participant, 53 BSA and 66 runners, responded to an online survey. The survey consisted of 3 sections and a total of 22 questions. Results: Runners were more knowledgeable than BSA in recommending RS for low arch, X2 (1, N=69) = 10.1, p<0.02 but not high arch X2 (1,N=69) = 3.253, p=0.071, and normal arch X2 = (1, N=69) = 1.468, p=0.226. Comfort, price and features were the top factors influencing RS purchase decisions for both BSA and runners. A comfortable RS was preferred to an aesthetically pleasing RS. Conclusions: Both runners and BSA lack the appropriate knowledge to select proper RS based on arch types. More education regarding RS should be given to these athletes. Comfort remains the top factor deciding purchase decisions.